Bhutan Macroeconomic and Public Finance Policy Note : Hydropower Impact and Public Finance Reforms towards Economic Self-Reliance - Boyreau, Genevieve; Rama, Martin (World Bank, Washington, DC, 2016)
Bhutan’s hydropower generation potential raises the prospect of tremendous development opportunities for the country: fast increasing export revenue, sustained economic growth, and rapid poverty reduction. Driven by developments in the hydropower sector, the country has grown at an average rate of 7 percent per year over the last decade, while poverty has declined remarkably fast. But hydropower development also creates significant challenges as follows: (i) macroeconomic instability; (ii) lack of self-reliance; and (iii) few private sector jobs. This policy note assesses the opportunities and challenges associated with hydropower development. It informs a possible strategy supportive of macroeconomic stability, fiscal self-reliance and private sector development. And it argues that fundamental changes in public finance, amounting to a paradigm shift, are central to the implementation of such strategy.